2006
DOI: 10.1089/lap.2006.16.582
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Coagulation and Fibrinolysis During Laparoscopic Cholecystectomy

Abstract: Reduced coagulation activity and increased fibrinolytic activity occur during and after laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In explaining this finding, increased mean PT following laparoscopic cholecystectomy surgery can be attributed to the activity of the patients' coagulation systems, and the fact that coagulation proteins and the laparoscopic technique may cause a highly severe catabolic liver response to the liver after the surgery (15). Additionally, the change in the PT factor is related to the laboratory kit, and the lack of change in the INR level is consistent with the results of a study carried out by Marakis et al (19). Concerning the relative stability of the INR level, it can be argued that the laparoscopic cholecystectomy can reduce the activation of the hemostatic mechanism, such that in the event of clotting, stimulates the fibrinolytic system and causes the release of a proteolytic enzyme called plasmin.…”
Section: Discussionsupporting
confidence: 87%
“…In explaining this finding, increased mean PT following laparoscopic cholecystectomy surgery can be attributed to the activity of the patients' coagulation systems, and the fact that coagulation proteins and the laparoscopic technique may cause a highly severe catabolic liver response to the liver after the surgery (15). Additionally, the change in the PT factor is related to the laboratory kit, and the lack of change in the INR level is consistent with the results of a study carried out by Marakis et al (19). Concerning the relative stability of the INR level, it can be argued that the laparoscopic cholecystectomy can reduce the activation of the hemostatic mechanism, such that in the event of clotting, stimulates the fibrinolytic system and causes the release of a proteolytic enzyme called plasmin.…”
Section: Discussionsupporting
confidence: 87%
“…Thromboembolic risks increase with those changes in hemostasis mechanism [ 19 ]. Despite PP, laparoscopic surgery has lower thromboembolic risks compared to open surgery [ 3 , 20 , 31 , 32 ]. Half of the postoperatively diagnosed DVT occurs during the surgical intervention itself.…”
Section: Discussionmentioning
confidence: 99%
“…An LC carries a low risk of DVT ( Blake, Toker & Dunn, 2001 ). Although INR, and fibrinogen increased in the 24th postoperative hour, affects and disturbs the coagulation cascade, there are studies that present contradictory findings ( Marakis et al, 2006 ). It has been shown that D-dimer was the only true sensitive marker of coagulation and fibrinolysis whereas the other parameters such as PT, APTT are indirect indicators of coagulation of fibrinolysis ( Milic et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%